Brassica Breeding and Biotechnology 2021
DOI: 10.5772/intechopen.94551
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Mustard (Brassica juncea) for Salt Tolerance: Problems and Prospects

Abstract: Salt stress is currently one of the most critical factors, reducing agricultural production. Indian mustard (Brassica juncea) is a major oilseed crop in these areas. However, salt affects as much as 50–90% worldwide yield reduction. Salt tolerance is a very complex factor controlled by a number of independent and/or interdependent mechanisms and genetic modification that lead to many changes in physiology and biochemistry at the cellular level. The classical methods of plant breeding for salt tolerance involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…As a result, with rising salt stress compared to the control, all RILs showed a significantly lower CO 2 assimilation rate (P < 0.05). Harmful effects of salinity on the photosynthetic system directly resulted in non‐stomatal suppression of photosynthesis, which is independent of stomatal closure, decreased stomatal conductance, and restricted availability of CO 2 for carboxylation process in the salt‐sensitive mustard RILs and sensitive parent (Singh et al, 2021). Other potential causes for the salinity‐induced decline in photosynthetic features include changes to cytoplasmic architectures, negative feedback of lower sink activity associated with sluggish transport of photosynthates, and changes in the activities of enzymes (Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, with rising salt stress compared to the control, all RILs showed a significantly lower CO 2 assimilation rate (P < 0.05). Harmful effects of salinity on the photosynthetic system directly resulted in non‐stomatal suppression of photosynthesis, which is independent of stomatal closure, decreased stomatal conductance, and restricted availability of CO 2 for carboxylation process in the salt‐sensitive mustard RILs and sensitive parent (Singh et al, 2021). Other potential causes for the salinity‐induced decline in photosynthetic features include changes to cytoplasmic architectures, negative feedback of lower sink activity associated with sluggish transport of photosynthates, and changes in the activities of enzymes (Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Different fatty acid compositions are crucial for the transportation of protective substances like glycine‐betaine. In the Indian mustard breeding program for seed quality criteria, the genotypes that demonstrated the high amount of oil, protein, crude fiber content, and least amount of increase in erucic acid content may be employed as possible donors (Singh et al, 2013; Singh et al, 2014; Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have reported that growing crops under saline conditions causes a significant reduction in plant and growth, crop yield (Zamani et al, 2011;Shanker et al, 2016;Priyanka et al, 2022;Harisha et al, 2022) as well as economic losses (Priyanka et al, 2020). The reduction in crop yield is mainly due to osmotic effects, specific ions effect, nutrient imbalance, and ion toxicity (Ankush et al, 2021;Singh et al, 2021). Proper selection of crop varieties, appropriate method of irrigation, on-farm agronomic practices, and adequate use of soil amendments, and other organic manures are suitable to sustain crop production in long term under poor quality water irrigation (Sharma and Minhas, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although, mustard is a salt tolerant crop among the oilseed crops, but their production is highly affected by salinity (Ashraf and McNeilly, 2004). However, the yield of mustard under saline water irrigation can be improved by cultivating the right salt tolerant varieties with balanced use of saline water (Singh et al, 2021). Ahmadi and Ardekhani, 2006 conducted a laboratory/greenhouse and field experiments to evaluate the -1 effects of salinity levels ranging from 1 to 12 dS m on germination rate, 8 leaf seedling dry matter, seed yield, and seed oil content of the 8 Canola (Brassica napus) cultivars: ACSN1, Falcon, Shirali, Ceres, Tower, Cobra, Global, and Oyerka.…”
Section: Introductionmentioning
confidence: 99%